A pilot study on the nature of "Sakitalis" a herbal dental medicament - Ballelos Jr., Ireneo R.; Bringas, Josef Ma. Karlos S.; de Leon, Arturo P. (Adviser).
Samples of the "sakitalis" suspension are procured from peddlers in Sta. Cruz, Manila. These samples are subjected to a series of test procedures. Testing are carried out to determine particular aspects of the said suspension in regards to its probable major components, sterility, and possible mucosal irritation. The tests required for this study are the following: Qualitative Analyses and Thin-layer Chromatography of the sample, Sterility Test, and Acute Eye Irritation Test. Corresponding results are achieved: upon qualitative analyses of the probable major components of the sample, there are no alkaloids present, tannins and terpenes are moderately present, while there are only traces of glycosides; thin-layer chromatography of the sample indicates the presence of camphor and the absence of eugenolo; sterility tests show negative cultures of aerobic, fungal, and anaerobic organisms; and the acute eye irritation test discloses minimal irritation of the samples. From here, therefore, the study can state the following: that camphor, tannins, and terpenes are several of the major components of the "sakitalis" suspension; that the suspension is sterile; and that it produces negligible amount of irritation to the oral mucosa.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Herbs -- Therapeutic use; Sakitalis -- Therapeutic use